A escrevivência como uma forma de reexistir: uma história encarnada de violência doméstica - Silva, Maria Nilza Rodrigues da (Universidade Federal do Tocantins, 2023)
The present work is a report of the experience of domestic violence against women. It tells through fiction through the writing method, the story of four women mixed with the story of the author of the present work. Its objectives were to study how psychology can contribute to support women victims of domestic violence, to research a way of constructing a narrative that enhances ways of re-existing the experience of domestic violence, to study the guidelines of the Federal Council of Psychology in caring for women in domestic violence situation. Therefore, it was possible to see that the rate of domestic violence is still alarming and that the protection and support networks still suffer from the lack of contribution from public policies, making it impossible for some municipalities to have this support and to look towards these services. We brought the different types of violence to better contextualize them through law nº 11.340, Lei Maria da Penha. Psychology has a fundamental and important role in this care and monitoring process, even through public welfare policies reporting the role and what should be done, we can see that it is still a very big challenge for these professionals, reporting the lack of training professionals, the tools needed to face these demands.